Evaluating Travel Distance to Radiation Facilities Among Rural and Urban Breast Cancer Patients in the Medicare Population. Issue 3 (17th December 2019) - Longacre, Colleen F.; Neprash, Hannah T.; Shippee, Nathan D.; Tuttle, Todd M.; Virnig, Beth A.
Abstract: Purpose: The distance patients travel for specialty care is an important barrier to health care access, particularly for those living in rural areas. This study characterizes the actual distance older breast cancer patients traveled to radiation treatment and the minimum distance necessary to reach radiation care, and examines whether any patient demographic or clinical factors are associated with greater travel distance. Methods: We used data from the Surveillance Epidemiology and End Results (SEER)‐Medicare database. Our cohort included 52, 317 women diagnosed with breast cancer between 2004 and 2013. Driving distances were calculated using Google Maps. We used generalized estimating equations to estimate associations between patient demographic and disease variables and travel distance. Findings: Patients living in rural areas traveled on average nearly 3 times as far as those from urban areas (40.8 miles vs 15.4 miles), and their nearest facility was more than 4 times farther away (21.9 miles vs 4.8 miles). Older age, being single or widowed, and lower household income were significantly associated with shorter actual travel distance, while increasing rurality was significantly associated with greater actual and minimum travel distance to radiation treatment. Disease severity (stage, grade, etc) was not significantly associated with actual or minimum travel distance. Conclusions: In this insured population, travel distance to radiation facilities may pose a significant burden for breast cancer patients, particularly among those living in rural areas. Policymakers and patient advocates should explore service delivery models, reimbursement models, and social supports aimed at reducing the impact of travel to radiation treatment for breast cancer patients.